2015
DOI: 10.1051/matecconf/20153001012
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Mechanical and Thermal Properties of PBT-TiO2Polymer Nanocomposite

Abstract: Abstract. This research aims to study the effects of the TiO2 in PBT composite fibers on the thermal properties, mechanical properties and photocatalytic properties of the polymer composite. The results showed that the tensile strength of the TiO2/PBT fibers decreased with increasing in the content of TiO2 in polymer matrix. The content of TiO2 in composite fibers did not affect the thermal properties of the fibers but the %crystalline of the composite fibers were increased with content of TiO2 in the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…As the fourth polymer for our study, we selected polybuthylene terephthalate (PBT), a semi-crystalline thermoplastic polymer that belongs to the polyester family, is characterized by its high rigidity, low tendency to creep, high strength, dimensional stability, good impact strength, very low thermal expansion coefficient, good wear and frictional resistance, good chemical resistance to acids, and very low moisture absorption, etc. PBT is mainly used in the automotive, consumer applications, electric, and textile industries and is very often modified with particulate fillers, like other polymers [ 12 , 13 ]. It was found that beta radiation crosslinking can significantly improve the mechanical properties, such as micro-hardness, indentation modulus, and indentation creep.…”
Section: Introductionmentioning
confidence: 99%
“…As the fourth polymer for our study, we selected polybuthylene terephthalate (PBT), a semi-crystalline thermoplastic polymer that belongs to the polyester family, is characterized by its high rigidity, low tendency to creep, high strength, dimensional stability, good impact strength, very low thermal expansion coefficient, good wear and frictional resistance, good chemical resistance to acids, and very low moisture absorption, etc. PBT is mainly used in the automotive, consumer applications, electric, and textile industries and is very often modified with particulate fillers, like other polymers [ 12 , 13 ]. It was found that beta radiation crosslinking can significantly improve the mechanical properties, such as micro-hardness, indentation modulus, and indentation creep.…”
Section: Introductionmentioning
confidence: 99%
“…From the obtained "load vs. depth of penetration" curves values of nano-indentation properties were calculated Table 2. The indentation hardness (H IT ) was calculated as maximum load (F max ) to the projected area of the hardness impression (A p ) and the indentation modulus (E IT ) is calculated from the Plane Strain modulus (E*) using an estimated sample Poisson's ratio (ν) according to [5][6][7][8]:…”
Section: Nano-indentation Testmentioning
confidence: 99%
“…PBT is suitable for injection molding or extrusion processes. For this reason, thermoplastic PBT composites [ 19 , 20 , 21 ] or PBT fiber composites (for capacitive touch panels, smartphones) [ 22 ] are often used in technical fields. In the medical field, PBT nonwovens are used for blood filtration, as carriers, absorbents [ 23 , 24 , 25 ], and also as technical cartilage tissue based on the used PBT fibers [ 26 ].…”
Section: Introductionmentioning
confidence: 99%